Structure and Mechanical and Technological Properties of Additive Material for Welding Heat-Resistant Steels - Efimenko, Mikola; Artemova, Svetlana; Penzev, Vladislav; Rozhnov, Oleksandr (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2020)
The analysis of casting defects in the hull parts of power equipment, and their elimination methods. The development directions of foreign researchers in the field of heat-resistant steels welding are established and analyzed. The prospects of using pearlite material for electric arc welding of defects is shown. The results of studies of the welding material of a pearlite structure, microalloyed by rare-earth metals, with high welding-technological, viscoplastic properties and impact strength are presented. An analysis of the state of scientific developments of metallurgists, material scientists and welders shows that, to ensure high viscoplastic properties of steel products, a promising direction is the use of rare earth metals as modifiers and microalloying additives as desulfurizers. The welding process is carried out without heating and subsequent heat treatment. For research, an experimental batch of electrodes was manufactured as rods in which the wire SV-08A was used. Doping was provided through an electrode coating. Alloying with rare-earth metals was carried out by introducing yttrium ligature into the coating, it was found that the introduction of rare-earth metals into the deposited metal allows to obtain high visco-plastic properties of the metal without reducing the carbon content, which, in turn, provides strength properties at the level specified by regulatory documentation.